Approach to the Egyptian presidential speech during the Arab Spring translated into Spanish. Two speeches by former president Hosni Mubarak as example (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
This article aims to shed light on the translation into Spanish of two speeches of the former Egyptian president Hosni Mubarak during the so-called Arab Spring published in El País. We try to approach the concept of political discourse and its characteristics, showing the peculiarities of Hosni Mubarak's two speeches from the point of view of discourse analysis. On the other hand, we clarify the outstanding problems in transmitting these two speeches from the Arabic language to the Spanish language. As well as, we analyze the strategies employed in their translation, relying on the model proposed by Chesterman (2016). It is highlighted that the translator resorted to some strategies that show manipulation in translation such as, informative modification, through addition and omission of information. In addition, the use of literal translation, modification of textual coherence and partial translation, among other strategies. Finally, we try to confirm that the translation of political discourse is a very complicated process that could involve some changes and manipulations and in which it is very difficult to achieve total equivalence.
Keywords: Arab Spring; Hosni Mubarak; political discourse; translation problems; translation strategies